Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae) - Seeman, Owen D. (Zootaxa, 2021)
Eutarsopolipus (Acari: Podapolipidae) is a large genus of mites parasitic in the subelytral space of carabid beetles. Herein, I explore the species radiations of Eutarsopolipus on the pterostichine genera Castelnaudia and Notonomus found in the rainforests of eastern Australia. Castelnaudia has an extraordinary radiation of podapolipid mite species, with most beetle species carrying multiple species of mites unique to each host. In contrast, each Notonomus species had just one species of Eutarsopolipus (with the exception of a single male mite of another species), and in four of the five host species examined, the single mite species could not be distinguished from each other. The host beetles and their new mite species are: Castelnaudia cordata with E. hebronae sp. nov., E. osculum sp. nov. and E. umbonatus sp. nov.; Castelnaudia eungella with E. savatus sp. nov.; Castelnaudia marginifera with E. labiatus sp. nov.; Castelnaudia mixta with E. mixtus sp. nov.; Castelnaudia porphyriaca with E. basiatus sp. nov., E. despoticus sp. nov. and E. teuceri sp. nov.; Castelnaudia septemcostata with E. nahmani sp. nov. and E. raveni sp. nov.; Castelnaudia setosiceps with E. hadros sp. nov.; Notonomus aurifer, N. dimorphicus, N. flos and N. spurgeoni with E. janus sp. nov.; and Notonomus transitus with E. biuncatus sp. nov.  All the described species from Castelnaudia were from the ochoai species group, and the species on Notonomus were from the leytei species group. Ten additional undescribed species were also found on these hosts, all in numbers insufficient for description: nine from Castelnaudia (ochoai and pterostichi species groups) and one from Notonomus (undetermined species group). Synhospitality was common on Castelnaudia, with four species of Eutarsopolipus on C. cordata, C. eungella, C. porphyriaca and three on C. septemcostata. Co-infestation was also common, with one-third of infested beetles hosting two or more species of Eutarsopolipus. I speculate that the greater longevity and slower speciation rates of Castelnaudia have permitted more successful host-switching and speciation of its parasites.